9th IGRSM International Conference and Exhibition on Geospatial & Remote Sensing (IGRSM 2018). (June 2018) - Unknown
Abstract : This proceeding consists of the peer-reviewed papers from the 9 th IGRSM International Conference and Exhibition on Geospatial & Remote Sensing & GIS (IGRSM 2018), which was organised by the Institution of Geospatial and Remote Sensing Malaysia (IGRSM) on 24-25 April 2018 at Berjaya Times Square Hotel, Kuala Lumpur, Malaysia. The conference, with the theme Geospatial Enablement, was aimed at disseminating knowledge and sharing expertise and experiences in geospatial sciences in all aspects of applications. It was also aimed to build linkages between local and international professionals in this field with industries.